(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Malyuga Elena Nikolaevna, Orlova Svetlana Nikolaevna The article is devoted to the study of lexical-pragmatic aspects of business interviews and question-answer communication blocks as the whole system of interdependent propositions which may have a great theoretical and practical potential and require special consideration peculiarities of this phenomenon. The article has also realized the relevant idea to define QACB and has submitted it to the structure of the business in the form of an interview scheme. Key words: business discourse, business interview, communicative unit, question-answer communicative unit (QACB).